All-Cause and Cause-Specific Mortality After Hypertensive Disease of Pregnancy. Issue 2 (August 2016) - Theilen, Lauren H.; Fraser, Alison; Hollingshaus, Michael S.; Schliep, Karen C.; Varner, Michael W.; Smith, Ken R.; Esplin, M. Sean
Abstract : OBJECTIVE: To assess whether women with a history of hypertensive disease of pregnancy have increased risk for early adult mortality. METHODS: In this retrospective cohort study, women with one or more singleton pregnancies (1939–2012) with birth certificate information in the Utah Population Database were included. Diagnoses were categorized into gestational hypertension; preeclampsia; hemolysis, elevated liver enzymes, and low platelet count syndrome; and eclampsia. Women with more than one pregnancy with hypertensive disease (exposed) were included only once, assigned to the most severe category. Exposed women were matched one to two to unexposed women by age, year of childbirth, and parity at the time of the index pregnancy. The causes of death were ascertained using Utah death certificates and the fact of death was supplemented with the Social Security Death Index. Hazard ratios for cause-specific mortality among exposed women compared with unexposed women were estimated using Cox regressions adjusting for neonatal sex, parental education, preterm delivery, race–ethnicity, and maternal marital status. RESULTS: A total of 60, 580 exposed women were matched to 123, 140 unexposed women; 4, 520 (7.46%) exposed and 6, 776 (5.50%) unexposed women had died by 2012. All-cause mortality was significantly higher among women with hypertensive disease of pregnancy (adjusted hazard ratio [HR] 1.65, 95% confidence interval [CI] 1.57–1.73). Exposed women's greatest excess mortality risks were from Alzheimer disease (adjusted HR 3.44, 95% CI 1.00–11.82), diabetes (adjusted HR 2.80, 95% CI 2.20–3.55), ischemic heart disease (adjusted HR 2.23, 95% CI 1.90–2.63), and stroke (adjusted HR 1.88, 95% CI 1.53–2.32). CONCLUSION: Women with hypertensive disease of pregnancy have increased mortality risk, particularly for Alzheimer disease, diabetes, ischemic heart disease, and stroke. Abstract : Supplemental Digital Content is Available in the Text.Women with hypertensive diseases of pregnancy have increased risk for early mortality, with the greatest risk of death from diabetes, Alzheimer disease, and cardiovascular disease.